EMPLOYEE LOYALTY : A SYSTEMATIC REVIEW OF THE LITERATURE - Maulana, M Iqbal (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Employee loyalty is an important factor in determining the success of the service and manufacturing sectors, with a profound effect on customer satisfaction and profitability. It is very important to continuously increase employee loyalty so as to achieve a significant competitive advantage, especially by minimizing the detrimental effects of high employee turnover. This study provides a detailed review of the methods and variables discussed in the peer-reviewed article on employee loyalty. Method: Through quantitative analysis, organization, and graphical representation of bibliometric data, including publication frequency and number of citations, derived from a thorough examination of the literature on in-depth analysis. Results: Our results provide essential insights and guidance for practitioners and scholars, aiming to navigate key achievements and hurdles in contemporary empirical investigations of employee loyalty. Novelty: It highlights shortcomings in current empirical research, suggests new paths for future studies, and identifies job loyalty gaps.